(untitled) (Abrahamic Religions: Jurnal Studi Agama-Agama, 2023)
This research illustrates the vulnerability experienced by contemporary society in practicing religious beliefs, necessitating the emergence of Theological Pluralism as a new innovation to provide space for minority communities such as the Baha’i to express their religious beliefs. The objective of this study is to elucidate the expressions and responses of the community towards the Baha’i community in Kubu Raya, viewed through the lens of Theological Pluralism. The research employs a qualitative approach rooted in sociology, incorporating literature review and field research. Data collection methods include observation, previous research, and relevant data pertaining to this study. This study indicate that the Baha’i community expresses its beliefs through social interactions viewed from the perspective of Theological Pluralism, ultimately fostering attitudes of tolerance, inclusivity, and appreciation for diversity within pluralistic societies. The community’s response to the Baha’i varies, with some exhibiting positive acceptance and others displaying negative rejection. Factors influencing these responses involve limitations in religious knowledge and the socio-political dynamics impacting religious domains.